Determination of the isotopic composition of micrometric uranium particles by UV femtosecond laser ablation coupled with sector-field single-collector ICP-MS. Issue 1 (20th October 2016) - Donard, A.; Pointurier, F.; Pottin, A.-C.; Hubert, A.; Pécheyran, C.
Abstract : In this article, performance of the coupling of a UV-fs-LA system with a high sensitivity ICP-MS for isotope analysis of individual micrometric uranium particles, including minor isotopes 234 U and 236 U, is discussed. Abstract : In this article, the coupling of a UV-fs-LA system with a sector-field ICP-MS for isotopic analysis of individual sub micrometric and micrometric uranium particles, especially for the measurement of minor isotopes ( 234 U and 236 U), is discussed. Ablation of uranium particles results in short (a few seconds) and highly noisy signals with sudden and extremely brief (<1 ms) increases in intensity (referred to as 'spikes'), making the precise determination of isotope ratios very challenging. Uranium particles were located beforehand by means of suitable techniques. Three isotope ratio calculation methods are evaluated. The influence of signal spikes on the accuracy and precision of the isotope ratios is discussed. Thanks to the implementation of a 'spike rejection filter', the measurement of uranium isotope ratios in particles from an isotopically certified reference material (NBS U010) is greatly improved. Measured ratios are in acceptable agreement with the reference values although a systematic bias was observed. Limits of detection of a few tens of attograms for minor isotopes are achieved. Isotopic mapping in the area around the initial ablation crater allows the observation of the deposition of debris. No isotope ratio bias is observed when analyzing uranium particles mixed with lead particles, showing that no significant lead-based polyatomic interference is produced. Results, including minor isotope ratios, obtained with particles of sizes from 0.3 to 1.5 μm sampled in a nuclear facility, are in good agreement with the values obtained by another well-established method for such analysis.